2011
DOI: 10.1007/s00292-011-1418-2
|View full text |Cite
|
Sign up to set email alerts
|

Gelenkendoprothesenpathologie

Abstract: Prosthesis durability has steadily increased with high 10-year rates of 88-95%. However, four pathogenetic groups of diseases can decrease prosthesis durability: (1) periprosthetic wear particle disease (aseptic loosening) (2) bacterial infection (septic loosening) (3) periprosthetic ossification, and (4) arthrofibrosis. The histopathological "extended consensus classification of periprosthetic membranes" includes four types of membranes, arthrofibrosis, and osseous diseases of endoprosthetics: The four types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
5
0
4
Order By: Relevance
“…These results were particularly associated with PJI. Many studies showed that the periprosthetic membrane is an ideal sample material for characterising the type of inflammation by histology, thus providing valuable evidence for the underlying cause of implant loosening [8, 24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were particularly associated with PJI. Many studies showed that the periprosthetic membrane is an ideal sample material for characterising the type of inflammation by histology, thus providing valuable evidence for the underlying cause of implant loosening [8, 24]. …”
Section: Discussionmentioning
confidence: 99%
“… F female, M male a Krenn et al [24] and Morawietz et al [9]: type I periprosthetic membrane (ppm) of the wear particle-induced type, type II ppm of the infectious type, type III ppm of the combined type, type IV indeterminate type…”
Section: Methodsmentioning
confidence: 99%
“…The treatment of periprosthetic infections is undisputed in case of peracute respectively high-grade infection [31]. An urgent revision surgery with evacuation of pus is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…[211] On the other hand, it has been described that a layer of connective tissue develops between the bone and prosthesis in both septic and aseptic loosening. [31214] And even well-fixed implants may have these membranes, even though they are considerably thinner. [1112] Several pathological mechanisms that may lead to loosening have been described and have been summarized in a histological classification which defines four types of periprosthetic membranes.…”
Section: Discussionmentioning
confidence: 99%
“…[1112] Several pathological mechanisms that may lead to loosening have been described and have been summarized in a histological classification which defines four types of periprosthetic membranes. [31215] The histological feature that suggests the pathological diagnosis of septic loosening is the presence of numerous inflammatory cells, particularly neutrophil polymorphonuclear leukocytes (neutrophils) in the periprosthetic membrane. Although the reliability of this investigation is questionable, it is agreed that the presence of numerous neutrophils in the periprosthetic tissue strongly correlates with septic loosening.…”
Section: Discussionmentioning
confidence: 99%